Self-assembly of 1T/1H superlattices in transition metal dichalcogenides - Chaojie Luo; Guohua Cao; Beilin Wang; Lili Jiang; Hengyi Zhao; Tongrui Li; Xiaolin Tai; Zhiyong Lin; Yue Lin; Zhe Sun; Ping Cui; Hui Zhang; et al. (Nature Communications)
Abstract Heterostructures and superlattices composed of layered transition metal dichalcogenides (TMDs), celebrated for their superior emergent properties over individual components, offer significant promise for the development of multifunctional electronic devices. However, conventional fabrication techniques for these structures depend on layer-by-layer artificial construction and are hindered by their complexity and inefficiency. Herein, we introduce a universal strategy for the automated synthesis of TMD superlattice single crystals through self-assembly, exemplified by the NbSe2-x Te x 1T/1H superlattice. The core principle of this strategy is to balance the formation energies of T (octahedral) and H (trigonal prismatic) phases. By adjusting the Te to Se stoichiometric ratio in NbSe2-x Te x , we reduce the formation energy disparity between the T and H phases, enabling the self-assembly of 1T and 1H layers into a 1T/1H superlattice. The resulting 1T/1H superlattices retain electronic characteristics of both 1T and 1H layers. We further validate the universality of this strategy by achieving 1T/1H superlattices through substituting Nb atoms in NbSe2 with V or Ti atoms. This self-assembly for superlattice crystal synthesis approach could extend to other layered materials, opening new avenues for efficient fabrication and broad applications of superlattices.